2019
DOI: 10.1108/jmd-01-2019-0022
|View full text |Cite
|
Sign up to set email alerts
|

Responsible management education in Egyptian public business schools

Abstract: Purpose Out of 24 public business schools in Egypt, the purpose of this paper is to focus on three in order to investigate how responsible management education is perceived and exercised by academics there. Design/methodology/approach A total of 168 academics were contacted and interviewed in 42 focus groups. The length of each focus group was about 45 min, and all of them were conducted in Arabic because the majority of respondents are not fluent in English. The authors used thematic analysis to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…org/) was ranked as having the lowest quality management education, Mousa et al (2019a) and Mousa et al (2020), have elaborated that unlike many Western business schools, tackling global responsibility and Rabasso, 2011;Waddock et al, 2010) highlight that the inclusion of sustainability in teaching and research scholarships at business schools has become the cornerstone in all accrediting bodies, such as Association to Advance Collegiate Schools of Business (AACSB) and European Quality Improvement System (EQUIS) evaluating business schools, the matter is seen different in the Middle East. Mousa et al (2019) indicate that public business schools in the Middle East are only accredited by the local governmental ministries of education in their countries. Accordingly, these schools can function without paying attention to or even being aware of some regulatory bodies, such as the AACSB.…”
Section: Rme In the Public Business Schools In Egypt And Similar Middle East Contextmentioning
confidence: 99%
See 3 more Smart Citations
“…org/) was ranked as having the lowest quality management education, Mousa et al (2019a) and Mousa et al (2020), have elaborated that unlike many Western business schools, tackling global responsibility and Rabasso, 2011;Waddock et al, 2010) highlight that the inclusion of sustainability in teaching and research scholarships at business schools has become the cornerstone in all accrediting bodies, such as Association to Advance Collegiate Schools of Business (AACSB) and European Quality Improvement System (EQUIS) evaluating business schools, the matter is seen different in the Middle East. Mousa et al (2019) indicate that public business schools in the Middle East are only accredited by the local governmental ministries of education in their countries. Accordingly, these schools can function without paying attention to or even being aware of some regulatory bodies, such as the AACSB.…”
Section: Rme In the Public Business Schools In Egypt And Similar Middle East Contextmentioning
confidence: 99%
“…Given the rapid worldwide spread of Covid-19 and the pessimistic expectations regarding some viruses in the near future, we suggest that business schools in Egypt and similar Middle Eastern countries establish units for sustaining RME. This unit will maintain a systemic set of practices to ensure academics understand what is appropriate and what is expected of them (Mousa et al, 2019). This will secure widely accepted ethical academic practices and contribute to the process of rebuilding the legitimacy of business schools (Scott et al, 2000).…”
Section: Managerial Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…We should also note that the results obtained seem even more positive against the background of the unsuccessful experience of other countries. For example, the analysis of the 3 leading business schools in Egypt revealed that they had problems associated with the introduction of a similar methodology [21].…”
Section: Literature Reviewmentioning
confidence: 99%